Anti-oxidation water-based lubricating coating material for hot extrusion of titanium and titanium alloy and preparation method of anti-oxidation water-based lubricating coating material
By designing a specific proportion of anti-oxidation water-based lubricating coating material, the problem that existing glass lubricants are difficult to uniformly coat in the range of 700 to 900°C is solved, and efficient hot extrusion molding of titanium and its alloys is achieved, reducing costs and simplifying subsequent processing.
Patent Information
- Application Number
- CN202411962667.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-22
AI Technical Summary
The existing glass lubricants are difficult to uniformly apply in the hot extrusion range of titanium and its alloys at 700 to 900°C, which affects the quality and efficiency of extrusion molding.
A lubricating coating material for hot extrusion of titanium and its alloys is designed to form a lubricating coating with high fluidity and adhesion through a specific proportion of base powder, deionized water and active additives.
In a high temperature environment of 700-900°C, the material can effectively reduce the friction coefficient, improve the quality and efficiency of extrusion molding, and has a low cost of use and is simple to follow-up processing.
Smart Images

Figure CN119859562A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of lubricants and relates to water-based lubricants, and specifically relates to an anti-oxidation water-based lubricating coating material for hot extrusion of titanium and its alloys and a preparation method thereof. Background Art
[0002] Titanium and its alloys are widely used in the fields of electronics, medical treatment, chemical industry, aerospace, etc. due to their excellent physical and chemical properties. They are ideal materials for producing bars, tubes and profiles. In the preparation process of non-ferrous metal tubes and bars, hot extrusion plays an important role as one of the leading methods.
[0003] However, titanium and its alloys face many challenges during the hot extrusion process: on the one hand, the extrusion temperature of titanium and its alloys is high and the yield strength is high, which can easily cause mold sticking problems; on the other hand, the quality of the lubrication link is directly related to the success or failure of the entire extrusion molding. Suitable lubricants can not only significantly reduce the peak extrusion pressure and extend the service life of the tools and dies, but also improve the yield rate and surface quality of the products, thereby achieving significant cost reduction and efficiency improvement. At present, glass lubrication is the most widely used method in the extrusion process of titanium and its alloys. It is low-cost, can provide good lubrication, and has excellent thermal insulation, anti-oxidation, and reduction of hydrogen and oxygen absorption during the heating process. Protective effects provide a guarantee for the performance and surface quality of extruded products.
[0004] However, it cannot be ignored that glass lubricants cannot fully cover the extrusion process requirements of titanium and its alloys. Specifically, glass lubricants are mostly used in high-temperature environments above 900°C, and glass lubrication is applied by rolling. Once the temperature is in the range of 700-900°C, it is difficult to evenly apply the glass lubricant to the workpiece surface because the temperature is lower than the melting point of the glass lubricant. Even the unmelted glass will have a negative impact during extrusion.
[0005] In view of this, there is an urgent need to design a new type of lubricant that can achieve the same lubrication effect as high-temperature glass lubricant in the extrusion range of 700-900°C. Summary of the invention
[0006] The purpose of the present invention is to overcome the shortcomings of the above-mentioned prior art and provide an anti-oxidation water-based lubricating coating material for hot extrusion of titanium and its alloys and a preparation method thereof, which has both lubrication and thermal protection properties under high temperature conditions (high temperature environment above 900°C); because of the strong adhesion between the material and the blank, the friction coefficient during non-ferrous metal extrusion can be effectively reduced, and the influence of the surrounding atmosphere during heating and insulation can be reduced, thereby reducing the extrusion pressure, improving production efficiency and yield rate; and the subsequent processing method is simple, economical and efficient.
[0007] To achieve the above object, the present invention provides the following technical solutions:
[0008] On the one hand, the present invention provides an anti-oxidation water-based lubricating coating material for hot extrusion of titanium and its alloys, which is formed by compounding a base powder, deionized water and an active additive in a mass ratio of (42.3-49.6): (47.7-53.6): (1.7-4.8);
[0009] The base powder comprises the following raw materials in parts by mass: 22.3 to 34.7 parts of graphite with a particle size of 500 to 2000 meshes; 21.3 to 40.5 parts of silicon dioxide with a particle size of 800 to 1500 meshes; 2.4 to 12.7 parts of aluminum oxide; 1.6 to 8.3 parts of potassium oxide and 1.3 to 9.6 parts of sodium oxide; 17.8 to 28.4 parts of sodium silicate or potassium silicate with a modulus of 2.0 to 2.8; and 5 to 12.5 parts of potassium hydroxide and / or sodium hydroxide.
[0010] Among them, graphite, as the main lubricating component, can effectively reduce the friction coefficient of titanium and its alloys during extrusion; adding sodium silicate or potassium silicate powder makes the solution have a certain viscosity, and can form a film on the surface of titanium and its alloys after coating and drying; adding silicon dioxide, aluminum oxide, potassium oxide, and sodium oxide can improve the strength during coating, increase toughness and weather resistance after drying and film formation, and at the same time, the dry coating can isolate the external atmosphere and improve the oxidation resistance during the heating process.
[0011] Specifically, the active additive includes the following raw materials in parts by weight: 32.8 to 43.6 parts of a wetting agent; 29.2 to 37.1 parts of a dispersant; 8.9 to 20.4 parts of a defoaming agent; and 7.5 to 21.6 parts of an antioxidant.
[0012] in:
[0013] The wetting agent comprises, by weight, 20.1 to 43.2 parts of sodium hydroxide, 18.7 to 35.1 parts of amide compounds, and 23.6 to 44.5 parts of sodium dodecyl sulfate or sodium dibutyl sulfonate.
[0014] The dispersant comprises, by weight, 34.3 to 52.6 parts of modified styrene maleic acid copolymer or polystyrene-poly (N-methyl-2-vinylpyridine) block copolymer, 11.5 to 21.9 parts of sodium carboxymethyl cellulose or ammonium salt solution of acrylate copolymer, and 27.8 to 44.2 parts of sodium dodecylbenzene sulfonate or polysulfonates.
[0015] The defoaming agent comprises, by weight: 17.6 to 33.2 parts of a carboxylamide defoaming agent, 15.2 to 21.7 parts of polyoxyethylene ether, and 22.8 to 51.3 parts of a silicone defoaming agent.
[0016] In terms of weight, the antioxidant comprises: 33.6 to 58.2 parts of sodium thiosulfate, 14.8 to 28.4 parts of water-soluble L-ascorbic acid, and 23.4 to 43.1 parts of disodium ethylenediaminetetraacetate or sodium pyrophosphate.
[0017] Furthermore, adding sodium hydroxide and / or potassium hydroxide, amides, sodium dodecyl sulfate or sodium dibutyl sulfonate can increase the graphite wetting angle, reduce the solution viscosity to improve fluidity and facilitate coating; adding modified styrene maleic acid copolymer or polystyrene-poly (N-methyl-2-vinyl pyridine) block copolymer, sodium carboxymethyl cellulose or acrylate copolymer ammonium salt solution, sodium dodecylbenzene sulfonate or polysulfonates can improve the dispersibility of insoluble solid powder in liquid, making the powder components more evenly dispersed. Adding antioxidants can increase the storage time of water-based lubricants, reduce the derivation rate of microorganisms inside water-based solutions, and provide a convenient storage method.
[0018] On the other hand, the present invention also provides a method for preparing the anti-oxidation water-based lubricating coating material for hot extrusion of titanium and its alloys as described in part or in whole above, which specifically comprises the following steps:
[0019] Step 1: preparing a base powder and an active additive respectively according to specific raw material composition and mass requirements, and homogenizing the base powder and the active additive;
[0020] Step 2, preparing the ingredients according to the required mass ratio, the mass ratio of the base powder, deionized water and active additive is (42.3-49.6): (47.7-53.6): (1.7-4.8);
[0021] Step 3, heating the deionized water to a specified temperature and then adding the base powder to perform homogenization. During the homogenization process, the active additive is added once at a specified time interval, and the amount of the active additive added each time does not exceed one third of the total amount of the active additive added;
[0022] Step 4: After the homogenization treatment is completed, the obtained liquid is fully stirred and mixed to complete the preparation of the anti-oxidation water-based lubricating coating material.
[0023] Specifically, in step 1, the base powder is homogenized by a three-dimensional mixer with a rotation speed of 10 to 24 rpm and a stirring time of 1 to 3 hours, which can avoid segregation, stratification and accumulation caused by different specific gravities of the components during the mixing process.
[0024] Specifically, in step 1, the homogenization treatment of the active additive is carried out by using an electric stirrer, the rotation speed of the electric stirrer is 50 to 200 rpm, and the stirring time is 5 to 10 minutes.
[0025] Specifically, in step 3, the deionized water uses deionized water with a resistivity of 0.5 to 18 MΩ at room temperature (25°C), and the specified temperature is 55 to 95°C; the homogenization treatment uses a homogenizer with a homogenization speed of 15000 to 20000 rpm, a homogenization time of not less than 30 minutes, and the specified time is 5 to 10 minutes.
[0026] Specifically, in step 4, the obtained liquid is transferred into an electric disperser for thorough stirring and mixing at a rotation speed of 100 to 500 rpm and a stirring time of 2 to 4 hours.
[0027] Compared with the prior art, the technical solution provided by the present invention has the following beneficial effects:
[0028] 1) The present invention is a hot extrusion lubricating and protective material formed based on specific raw materials and parts by mass, wherein: graphite is compounded with the above-mentioned other powders as the main lubricating component and homogenized, and then the base powder is added to the heated deionized water, and the sodium silicate or potassium silicate gradually dissolves during the stirring process, so that the solution has a certain viscosity. When using it for coating: the insoluble substances in the base powder can be coated, and a lubricating coating can be formed on the surface of titanium and its alloys after drying, and the outermost layer is a dense SiO2 film. At the same time, the addition amount of sodium silicate or potassium silicate needs to be controlled within a certain range (17.8 to 28.4 parts by mass), otherwise excessive dissolution will cause the viscosity of the solution to increase, and the coating after drying is very easy to crack. The graphite in the inner layer plays the main lubricating role, and silicon dioxide, aluminum oxide, potassium oxide or sodium oxide as aggregates can enhance the weather resistance and strength of the coating, but the addition amount should not be too large, otherwise it will directly affect the lubrication performance. At the same time, a certain amount of active additives are added regularly. The wetting agent can increase the wetting angle of insoluble substances such as graphite, reduce the viscosity of the solution, and improve fluidity and leveling. The dispersant can make the insoluble powder particles evenly arranged in the solution. Under the action of the defoamer, the coating can be flat and bubble-free. The antioxidant is to slow down the derivation rate of microorganisms in the water and extend the storage time. The above components work together to eventually make the solution have strong fluidity, good leveling, and uniform distribution of particles, and have a certain strength after coating and drying.
[0029] 2) The antioxidant water-based lubricating coating material provided by the present invention has raw material composition and equipment used in the preparation process that can be obtained in the industrial market, has a simple preparation process, has good lubrication effect (at 700-900°C, the friction factor measured by a rotary friction and wear tester is 0.191-0.202), has high fluidity, high adhesion and good antioxidant properties.
[0030] In summary, the anti-oxidation water-based lubricating coating material provided by the present invention can reduce its use cost by 40% to 60% compared with glass powder lubrication, and is convenient and quick in the blank lubrication preparation stage, saving labor costs and improving production efficiency. The subsequent treatment of the residual lubricant after hot extrusion is simple, for example, it can be easily removed by simple cleaning, cutting, grinding, etc., and has good economy and high environmental protection. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] The accompanying drawings are incorporated in and constitute a part of this specification and, together with the description, serve to explain the principles of the present invention.
[0032] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.
[0033] Figure 1 A flow chart of the preparation method of the anti-oxidation water-based lubricating coating material provided by the present invention;
[0034] Figure 2 This is a surface state diagram of a TA2 titanium extrusion product obtained by applying the anti-oxidation water-based lubricating coating material in Example 1;
[0035] Figure 3 This is a test curve of the friction coefficient of the TA2 titanium extrusion product surface obtained by a rotary friction and wear tester at 700-900°C;
[0036] FIG4 is a test result of white light interference of wear marks after the surface friction and wear test of TA2 titanium extrusion products is completed: FIG4(a) is a cross-sectional height data curve corresponding to the three-dimensional scanning of the wear marks, FIG4(b) is a three-dimensional scanning image of the wear marks, and FIG4(c) is a top view of the three-dimensional scanning image of the wear marks;
[0037] Figure 5 This is a surface state diagram of a TA10 titanium extrusion product obtained by applying the anti-oxidation water-based lubricating coating material in Example 2;
[0038] Figure 6 This is a surface state diagram of a TC2 titanium extrusion product obtained by applying the anti-oxidation water-based lubricating coating material in Example 3;
[0039] Figure 7 This is a surface state diagram of the TC2 titanium extruded product made using traditional glass lubricant as a comparative example. DETAILED DESCRIPTION
[0040] Here, exemplary embodiments will be described in detail, and the embodiments described in the following exemplary embodiments do not represent all embodiments consistent with the present invention. Instead, they are only examples consistent with some aspects of the present invention described in detail in the appended claims.
[0041] In order to enable the water-based lubricant to achieve the same lubrication effect as the high-temperature glass lubricant in the extrusion range of 700-900°C, the present invention provides an anti-oxidation water-based lubricating coating material for hot extrusion of titanium and its alloys, which is compounded with a base powder, deionized water and an active additive in a mass ratio of (42.3-49.6): (47.7-53.6): (1.7-4.8);
[0042] The base powder comprises the following raw materials in parts by mass: 22.3 to 34.7 parts of graphite with a particle size of 500 to 2000 meshes; 21.3 to 40.5 parts of silicon dioxide with a particle size of 800 to 1500 meshes; 2.4 to 12.7 parts of aluminum oxide; 1.6 to 8.3 parts of potassium oxide and 1.3 to 9.6 parts of sodium oxide; 17.8 to 28.4 parts of sodium silicate or potassium silicate with a modulus of 2.0 to 2.8; and 5 to 12.5 parts of potassium hydroxide and / or sodium hydroxide.
[0043] Specifically, the active additive includes the following raw materials in parts by weight: 32.8 to 43.6 parts of a wetting agent; 29.2 to 37.1 parts of a dispersant; 8.9 to 20.4 parts of a defoaming agent; and 7.5 to 21.6 parts of an antioxidant.
[0044] in:
[0045] The wetting agent comprises, by weight, 20.1 to 43.2 parts of sodium hydroxide, 18.7 to 35.1 parts of amide compounds, and 23.6 to 44.5 parts of sodium dodecyl sulfate or sodium dibutyl sulfonate.
[0046] The dispersant comprises, by weight, 34.3 to 52.6 parts of modified styrene maleic acid copolymer or polystyrene-poly (N-methyl-2-vinylpyridine) block copolymer, 11.5 to 21.9 parts of sodium carboxymethyl cellulose or ammonium salt solution of acrylate copolymer, and 27.8 to 44.2 parts of sodium dodecylbenzene sulfonate or polysulfonates.
[0047] The defoaming agent comprises, by weight: 17.6 to 33.2 parts of a carboxylamide defoaming agent, 15.2 to 21.7 parts of polyoxyethylene ether, and 22.8 to 51.3 parts of a silicone defoaming agent.
[0048] In terms of weight, the antioxidant comprises: 33.6 to 58.2 parts of sodium thiosulfate, 14.8 to 28.4 parts of water-soluble L-ascorbic acid, and 23.4 to 43.1 parts of disodium ethylenediaminetetraacetate or sodium pyrophosphate.
[0049] On the other hand, the present invention also provides a method for preparing the anti-oxidation water-based lubricating coating material for hot extrusion of titanium and its alloys as described in part or in whole above, which specifically comprises the following steps:
[0050] Step 1: preparing a base powder and an active additive respectively according to specific raw material composition and mass requirements, and homogenizing the base powder and the active additive;
[0051] Step 2, preparing the ingredients according to the required mass ratio, the mass ratio of the base powder, deionized water and active additive is (42.3-49.6): (47.7-53.6): (1.7-4.8);
[0052] Step 3, heating the deionized water to a specified temperature and then adding the base powder to perform homogenization. During the homogenization process, the active additive is added once at a specified time interval, and the amount of the active additive added each time does not exceed one third of the total amount of the active additive added;
[0053] Step 4: After the homogenization treatment is completed, the obtained liquid is fully stirred and mixed to complete the preparation of the anti-oxidation water-based lubricating coating material.
[0054] Specifically, in step 1, the base powder is homogenized by a three-dimensional mixer with a rotation speed of 10 to 24 rpm and a stirring time of 1 to 3 hours, which can avoid segregation, stratification and accumulation caused by different specific gravities of the components during the mixing process.
[0055] Specifically, in step 1, the homogenization treatment of the active additive is carried out by using an electric stirrer, the rotation speed of the electric stirrer is 50 to 200 rpm, and the stirring time is 5 to 10 minutes.
[0056] Specifically, in step 3, the deionized water uses deionized water with a resistivity of 0.5 to 18 MΩ at room temperature (25°C), and the specified temperature is 55 to 95°C; the homogenization treatment uses a homogenizer with a homogenization speed of 15000 to 20000 rpm, a homogenization time of not less than 30 minutes, and the specified time is 5 to 10 minutes.
[0057] Specifically, in step 4, the obtained liquid is transferred into an electric disperser for thorough stirring and mixing at a rotation speed of 100 to 500 rpm and a stirring time of 2 to 4 hours.
[0058] In order to enable those skilled in the art to better understand the technical solution of the present invention, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments.
[0059] Example 1 (Application of Anti-Oxidation Water-Based Lubricating Coating Material in Hot Extrusion TA2 Titanium Ingot Process)
[0060] See also Figure 1 As shown, this embodiment provides an anti-oxidation water-based lubricating coating material for hot extrusion of titanium and its alloys, which is formed by compounding basic powder, deionized water and active additives in a mass ratio of 47:50:3; wherein,
[0061] The base powder was weighed and prepared according to the following mass parts: 33 parts of graphite powder with a particle size of 1500 mesh, 22 parts of silicon dioxide with a particle size of 1000 mesh, 10 parts of aluminum oxide, 4 parts of potassium oxide, 7 parts of sodium oxide, 6 parts of sodium hydroxide, and 18 parts of sodium silicate powder with a modulus of 2.0 were weighed, all of which were transferred into a three-dimensional mixer, the spindle speed was set to 15 rpm, and stirred for 1.5 hours;
[0062] The active additives were weighed and prepared according to the following mass parts: 33 parts of wetting agent, 36 parts of dispersant, 16 parts of defoaming agent, and 15 parts of antioxidant were weighed and transferred into a homogenizer, the stirring speed was set to 150 rpm, and stirred for 10 minutes to obtain a uniform active additive;
[0063] Specifically, the specific composition of each component in the active additive is as follows: by mass (100 parts), the wetting agent is formed by compounding 21 parts of sodium hydroxide, 35 parts of amide compounds, and 44 parts of sodium dodecyl sulfate; the dispersant is formed by compounding 35 parts of modified styrene maleic acid copolymer, 21 parts of sodium carboxymethyl cellulose, and 44 parts of sodium dodecylbenzene sulfonate; the defoamer is formed by compounding 33 parts of carboxyamide defoamers, 20 parts of polyoxyethylene ether, and 47 parts of silicone defoamers; the antioxidant is formed by compounding 34 parts of sodium thiosulfate, 23 parts of water-soluble L-ascorbic acid, and 43 parts of disodium ethylenediaminetetraacetate;
[0064] Deionized water with a resistivity of 0.5 MΩ at room temperature (25°C) was used and heated to 75°C. After reaching the temperature, the base powder was added and homogenized using a homogenizer (homogenizing speed of 15000 rpm) for 40 minutes. During the homogenization process, the active additive was added once every 8 minutes, and the single addition amount was one-fifth of the total amount of active additives. After the homogenization was completed, the liquid was transferred to an electric disperser, the speed was set to 200 rpm, and the stirring was carried out for 3 hours to finally obtain an anti-oxidative water-based lubricating coating material (I).
[0065] In addition, this embodiment also provides the application of the above-mentioned anti-oxidation water-based lubricating coating material (I) in the hot extrusion TA2 titanium ingot process, and the specific process is as follows:
[0066] The pure titanium ingot is sandblasted to achieve a surface roughness Ra of 3.2 to 6.3 μm, and the pure titanium ingot is cleaned in an ultrasonic cleaning tank with a metal degreasing agent to improve the bonding strength between the anti-oxidation water-based lubricating coating material (I) and the surface during subsequent lubrication;
[0067] The prepared anti-oxidation water-based lubricating solution is placed in a special container, and the pure titanium ingot is completely soaked in it for 3 to 5 seconds and then taken out to evenly coat the surface with the water-based lubricating coating material. After drying at room temperature for 3.5 hours, hot extrusion is carried out. The extrusion temperature is 730℃, the extruded tube specification is Ф50×12mm (outer diameter is 50mm, wall thickness is 12mm), the extrusion ratio is 12, and the pressure is stable during the entire extrusion process. The surface of the obtained TA2 titanium extruded product has no obvious defects such as grooves and cracks. The surface state diagram is shown in Figure 2 .
[0068] In addition, the inventors of the present application conducted a friction test on the water-based lubricating coating material obtained in Example 1. The test conditions were to operate the water-based lubricating coating material in an environment of 700 to 900°C using a rotary friction and wear tester. Finally, the average value of the friction factor was found to be 0.191 to 0.202 (see Figure 3 ); FIG4 is the test result of white light interference of wear marks after the surface friction and wear test of TA2 titanium extrusion products is completed: FIG4(a) is a cross-sectional height data curve corresponding to the three-dimensional scanning of the wear marks, FIG4(b) is a three-dimensional scanning image of the wear marks, and FIG4(c) is a top view of the three-dimensional scanning image of the wear marks; Figure 4(a) to Figure 4(c) It can be seen that the water-based lubricating coating material has a good lubricating effect, the wear scar is relatively smooth without exposing the base material, the wear scar width is only 0.50 mm, and the wear scar depth is only 0.045 mm.
[0069] Example 2 (Application of Anti-Oxidation Water-Based Lubricating Coating Material in Hot Extrusion TA10 Titanium Ingot Process)
[0070] This embodiment provides an anti-oxidation water-based lubricating coating material for hot extrusion of titanium and its alloys, which is composed of a base powder, deionized water and an active additive, and the mass ratio of the three is 48:48:4; wherein,
[0071] The base powder was weighed and prepared according to the following mass parts: 23 parts of graphite powder with a particle size of 500 mesh, 30 parts of silicon dioxide with a particle size of 800 mesh, 6 parts of aluminum oxide, 6 parts of potassium oxide, 4 parts of sodium oxide, 20 parts of potassium silicate powder with a modulus of 2.0, 6 parts of sodium hydroxide, and 5 parts of potassium hydroxide were weighed, all of which were transferred into a three-dimensional mixer, the spindle speed was set to 10 rpm, and stirred for 3 hours;
[0072] The active additives were weighed and prepared according to the following mass parts: 42 parts of wetting agent, 32 parts of dispersant, 15 parts of defoaming agent, and 11 parts of antioxidant were weighed and transferred into a homogenizer, the stirring speed was set to 200 rpm, and stirred for 8 minutes to obtain a uniform active additive;
[0073] Specifically, the specific composition of each component in the active additive is as follows: by weight (100 parts), the wetting agent is formed by compounding 43 parts of sodium hydroxide, 19 parts of amide compounds, and 38 parts of dibutyl sodium sulfonate; the dispersant is formed by compounding 52 parts of polystyrene-poly (N-methyl-2-vinylpyridine) block copolymer, 12 parts of ammonium salt solution of acrylate copolymer, and 36 parts of polysulfonate; the defoamer is formed by compounding 28 parts of carboxylamide defoamer, 21 parts of polyoxyethylene ether, and 51 parts of silicone defoamer; the antioxidant is formed by compounding 58 parts of sodium thiosulfate, 15 parts of water-soluble L-ascorbic acid, and 27 parts of sodium pyrophosphate;
[0074] Deionized water with a resistivity of 9 MΩ at room temperature (25°C) was used and heated to 55°C. After reaching the temperature, the base powder was added and homogenized using a homogenizer (homogenizing speed 20000 rpm) for 30 minutes. During the homogenization process, the active additive was added once every 10 minutes, and the single addition amount was one third of the total amount of the active additive. After the homogenization was completed, the liquid was transferred to an electric disperser, the speed was set to 500 rpm, and the stirring was carried out for 2 hours to finally obtain an anti-oxidative water-based lubricating coating material (II).
[0075] In addition, this embodiment also provides the application of the above-mentioned anti-oxidation water-based lubricating coating material (II) in the hot extrusion TA10 titanium ingot process, and the specific process is as follows:
[0076] The TA10 titanium ingot is sandblasted to a surface roughness Ra of 3.2 to 6.3 μm, and the TA10 titanium ingot is cleaned in an ultrasonic cleaning tank with a metal degreasing agent to improve the bonding strength between the anti-oxidation water-based lubricating coating material (II) and the surface during subsequent lubrication;
[0077] The prepared anti-oxidation water-based lubricating solution is placed in a special container, and the TA10 titanium ingot is completely soaked in it for 3 to 5 seconds and then taken out to evenly coat the surface with the water-based lubricating coating material. After drying at room temperature for 3.5 hours, hot extrusion is performed. The extrusion temperature is 800°C, the extruded tube specification is Ф130×10mm (outer diameter is 130mm, wall thickness is 10mm), the extrusion ratio is 11, and the pressure is stable during the entire extrusion process. The surface of the obtained TA10 titanium extruded product has no obvious defects such as grooves and cracks. The surface state diagram is shown in Figure 5 .
[0078] Example 3 (Application of Anti-Oxidation Water-Based Lubricating Coating Material in Hot Extrusion TC2 Titanium Ingot Process)
[0079] This embodiment provides an anti-oxidation water-based lubricating coating material for hot extrusion of titanium and its alloys, which is composed of a base powder, deionized water and an active additive, and the mass ratio of the three is 45:53:2; wherein,
[0080] The base powder was weighed and prepared according to the following mass parts: 28 parts of graphite powder with a particle size of 2000 mesh, 40 parts of silicon dioxide with a particle size of 1500 mesh, 3 parts of aluminum oxide, 3 parts of potassium oxide, 2 parts of sodium oxide, 28 parts of sodium silicate powder with a modulus of 2.8, 7 parts of sodium hydroxide, and 5 parts of sodium hydroxide were weighed and all transferred into a three-dimensional mixer, the spindle speed was set to 24 rpm, and stirred for 1 hour;
[0081] The active additives were weighed and prepared according to the following mass parts: 38 parts of wetting agent, 33 parts of dispersant, 12 parts of defoaming agent, and 17 parts of antioxidant were weighed and transferred into a homogenizer, the stirring speed was set to 300 rpm, and stirred for 5 minutes to obtain a uniform active additive;
[0082] Specifically, the specific composition of each component in the active additive is as follows: by mass (100 parts), the wetting agent is formed by compounding 30 parts of sodium hydroxide, 28 parts of amide compounds, and 42 parts of sodium dodecyl sulfate or sodium dibutyl sulfonate; the dispersant is formed by compounding 51 parts of modified styrene maleic acid copolymer or polystyrene-poly (N-methyl-2-vinylpyridine) block copolymer, 21 parts of sodium carboxymethyl cellulose or ammonium salt solution of acrylate copolymer, and 28 parts of polysulfonate; the defoamer is formed by compounding 32 parts of carboxylamide defoamer, 18 parts of polyoxyethylene ether, and 50 parts of silicone defoamer; the antioxidant is formed by compounding 48 parts of sodium thiosulfate, 28 parts of water-soluble L-ascorbic acid, and 24 parts of sodium pyrophosphate;
[0083] Deionized water with a resistivity of 18 MΩ at room temperature (25°C) was used and heated to 95°C. After reaching the temperature, the base powder was added and homogenized using a homogenizer (homogenizing speed of 18000 rpm) for 40 minutes. During the homogenization process, the active additive was added once every 5 minutes, and the single addition amount was one eighth of the total amount of active additives. After the homogenization was completed, the liquid was transferred to an electric disperser, the speed was set to 100 rpm, and the stirring was carried out for 4 hours to finally obtain an anti-oxidative water-based lubricating coating material (III).
[0084] In addition, this embodiment also provides the application of the above-mentioned anti-oxidation water-based lubricating coating material (III) in the hot extrusion TC2 titanium ingot process, and the specific process is as follows:
[0085] The TC2 titanium ingot is sandblasted to a surface roughness Ra of 3.2 to 6.3 μm, and the TC2 titanium ingot is cleaned in an ultrasonic cleaning tank with a metal degreasing agent to improve the bonding strength between the anti-oxidation water-based lubricating coating material (III) and the surface during subsequent lubrication;
[0086] The prepared anti-oxidation water-based lubricating solution is placed in a special container, and the TC2 titanium ingot is completely soaked in it for 3 to 5 seconds before being taken out to evenly coat the surface with the water-based lubricating coating material. After drying at room temperature for 3.5 hours, hot extrusion is performed. The extrusion temperature is 900°C, the extruded tube specification is Ф158×23mm (outer diameter is 158mm, wall thickness is 23mm), the extrusion ratio is 5, and the pressure is stable during the entire extrusion process. The surface of the obtained TC2 titanium extruded product has no obvious defects such as grooves and cracks. The surface state diagram is shown in FIG. Figure 6 .
[0087] Comparative Example
[0088] This comparative example provides the application of the existing glass lubricant in the extrusion of TC2 alloy bars with a specification of Ф158mm×23mm. The extrusion temperature is 1000℃. The surface state of the extruded product is shown in FIG. Figure 7 The grooves are deep, the oxidation is serious, and there are cracks at the ends, which cannot meet the use requirements of the product.
[0089] The above description is only a specific embodiment of the present invention, so that those skilled in the art can understand or implement the present invention. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present invention.
[0090] It should be understood that the present invention is not limited to what has been described above and that various modifications and changes may be made without departing from its scope. The scope of the present invention is limited only by the appended claims.
Claims
1. An anti-oxidation water-based lubricating coating material for hot extrusion of titanium and its alloys, characterized in that: The base powder, deionized water and active additives are compounded in a mass ratio of (42.3-49.6): (47.7-53.6): (1.7-4.8); The base powder comprises the following raw materials in parts by mass: 22.3 to 34.7 parts of graphite with a particle size of 500 to 2000 meshes; 21.3 to 40.5 parts of silicon dioxide with a particle size of 800 to 1500 meshes; 2.4 to 12.7 parts of aluminum oxide; 1.6 to 8.3 parts of potassium oxide and 1.3 to 9.6 parts of sodium oxide; 17.8 to 28.4 parts of sodium silicate or potassium silicate with a modulus of 2.0 to 2.8; and 5 to 12.5 parts of potassium hydroxide and / or sodium hydroxide.
2. The anti-oxidation water-based lubricating coating material for hot extrusion of titanium and its alloys according to claim 1, characterized in that: The active additive comprises the following raw materials in parts by weight: 32.8 to 43.6 parts of a wetting agent; 29.2 to 37.1 parts of a dispersant; 8.9 to 20.4 parts of a defoaming agent; and 7.5 to 21.6 parts of an antioxidant.
3. The anti-oxidation water-based lubricating coating material for hot extrusion of titanium and its alloys according to claim 2, characterized in that: The wetting agent comprises, by weight, 20.1 to 43.2 parts of sodium hydroxide, 18.7 to 35.1 parts of amide compounds, and 23.6 to 44.5 parts of sodium dodecyl sulfate or sodium dibutyl sulfonate.
4. The anti-oxidation water-based lubricating coating material for hot extrusion of titanium and its alloys according to claim 2, characterized in that: The dispersant comprises, by weight, 34.3 to 52.6 parts of modified styrene maleic acid copolymer or polystyrene-poly (N-methyl-2-vinylpyridine) block copolymer, 11.5 to 21.9 parts of sodium carboxymethyl cellulose or ammonium salt solution of acrylate copolymer, and 27.8 to 44.2 parts of sodium dodecylbenzene sulfonate or polysulfonates.
5. The anti-oxidation water-based lubricating coating material for hot extrusion of titanium and its alloys according to claim 2, characterized in that: The defoaming agent comprises, by weight: 17.6 to 33.2 parts of a carboxylamide defoaming agent, 15.2 to 21.7 parts of polyoxyethylene ether, and 22.8 to 51.3 parts of a silicone defoaming agent.
6. The anti-oxidation water-based lubricating coating material for hot extrusion of titanium and its alloys according to claim 2, characterized in that: In terms of weight, the antioxidant comprises: 33.6 to 58.2 parts of sodium thiosulfate, 14.8 to 28.4 parts of water-soluble L-ascorbic acid, and 23.4 to 43.1 parts of disodium ethylenediaminetetraacetate or sodium pyrophosphate.
7. A method for preparing an anti-oxidation water-based lubricating coating material for hot extrusion of titanium and its alloys as claimed in any one of claims 1 to 6, characterized in that: The specific steps include: Step 1: preparing a base powder and an active additive respectively according to specific raw material composition and mass requirements, and homogenizing the base powder and the active additive; Step 2, preparing the ingredients according to the required mass ratio, the mass ratio of the base powder, deionized water and active additive is (42.3-49.6): (47.7-53.6): (1.7-4.8); Step 3, heating the deionized water to a specified temperature and then adding the base powder to perform homogenization. During the homogenization process, the active additive is added once at a specified time interval, and the amount of the active additive added each time does not exceed one third of the total amount of the active additive added; Step 4: After the homogenization treatment is completed, the obtained liquid is fully stirred and mixed to complete the preparation of the anti-oxidation water-based lubricating coating material.
8. The method for preparing the anti-oxidation water-based lubricating coating material for hot extrusion of titanium and its alloys according to claim 7, characterized in that: In step 1, The base powder is homogenized by a three-dimensional mixer, the rotation speed of the three-dimensional mixer is 10 to 24 rpm, and the stirring time is 1 to 3 hours; The homogenization treatment of the active additive is carried out by an electric stirrer, the rotation speed of the electric stirrer is 50 to 200 rpm, and the stirring time is 5 to 10 minutes.
9. The method for preparing the anti-oxidation water-based lubricating coating material for hot extrusion of titanium and its alloys according to claim 7, characterized in that: In step 3, the deionized water uses deionized water with a resistivity of 0.5 to 18 MΩ at room temperature, and the specified temperature is 55 to 95° C.; the homogenization treatment uses a homogenizer with a homogenization speed of 15000 to 20000 rpm, a homogenization time of not less than 30 minutes, and the specified time is 5 to 10 minutes.
10. The method for preparing the anti-oxidation water-based lubricating coating material for hot extrusion of titanium and its alloys according to claim 7, characterized in that: In step 4, the obtained liquid is transferred into an electric dispersing stirrer for thorough stirring and mixing at a rotation speed of 100 to 500 rpm for a stirring time of 2 to 4 hours.